Modeling of the Diffusion Bond for SPF/DB Titanium Hollow Structures - Xianghai Chai; Xiaoyun Zhang; Zhiqiang Wang; Yesheng Liu (International Journal of Aerospace Engineering)
Diffusion-bonded titanium hollow warren structures have been successfully applied in aircraft engine components, such as fan blade, and OGV, while the optimal design of the hollow warren structure to improve its impact resistance, especially under bird-strike event, has been a challenge. In this work, a series of impact tests and numerical simulations are carried out to investigate the effect of key geometric features on the overall impact strength of a panel-shaped titanium hollow warren structure. Based on experimental and numerical studies, a quantitative relationship between diffusion bonding seam strength and the overall impact strength is developed. Meanwhile, key geometric factors affecting the resultant bonding seam strength for a typical manufacturing process are identified. This work provides useful references for the optimal design to increase impact resistance for aircraft engine hollow warren structure components.